Updated list of Anopheles species (Diptera: Culicidae) by country in the Afrotropical Region and associated islands - Irish, Seth R.; Kyalo, David; Snow, Robert W.; Coetzee, Maureen (Zootaxa, 2020)
The distributions of the Afrotropical Anopheles mosquitoes were first summarized in 1938. In 2017, an extensive geo-coded inventory was published for 48 sub-Saharan African countries, including information such as sampling methods, collection dates, geographic co-ordinates and the literature consulted to produce the database. Using the information from the 2017 inventory, earlier distribution lists, museum collections and publications since 2016, this paper presents an updated, simplified list of Anopheles species by mainland countries and associated Afrotropical islands, with comments where applicable. It is intended as a supplement to the 2017 geo-coded inventory.